The FDP/FIB Ratio and Blood FDP Level May Be Related to Seizures After Fever in Young Children - Li, Chun; Ma, Weining; Li, Shaoyi; Zhao, Yajuan; Zhao, Xuyang; Wang, Hua (Frontiers in Pediatrics, 2020)
Objective To evaluate the relationship of the blood fibrinogen (FIB) degradation product (FDP) level and FDP/FIB ratio with seizure in young children with fever. Methods A total of 35 children with simple febrile seizures and 80 children with fever but no seizure were selected. First, the differences in white blood cell (WBC), platelets (PLT), prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time (TT), FIB, FDP, ,FDP/FIB ratio, and C-reactive protein (CRP) between 35 children with simple febrile seizures and 40 randomly selected children with fever but no seizure were retrospectively analyzed. Then, an ROC curve was used to determine the diagnostic utility of the FDP level, FDP/FIB ratio, and FDP+FDP/FIB ratio, and the best diagnostic cutoff points were selected. Finally, the diagnostic specificities of the three diagnostic indicators were verified by comparison with the results of all 80 children with fever but no seizure. Results The FDP level and FDP/FIB ratio were significantly different between the two groups (P < 0.0001) and there was a positive correlation between the FDP and FIB levels. Both the FDP level and FDP/FIB ratio had good diagnostic value. An FDP ≥ 2.0 mg/L and FDP/FIB ratio ≥ 0.5 had good diagnostic specificities. Combined application of an FDP ≥ 2.0 mg/L and FDP/FIB ratio ≥ 0.5 improved the diagnostic power. Conclusions The blood FDP level and FDP/FIB ratio may be related to seizures after fever, and an FDP ≥ 2.0 mg/L + FDP/FIB ratio ≥ 0.5 has good diagnostic specificity.